An Effectiveness Of Mycorrhia And Lime Application On The Growth Of Oil Palm Seedlings (Elaeis Guineensis Jacq) In Peat Soil - Hafiz Ahmad (Sean Institute, 2025)
High interest in developing oil palm plantations increases land value and relaxes land suitability criteria. Flat topography, specifically peatlands, has been targeted as potential new areas for development since the 1990s. Peatlands are acidic, so improving soil pH with lime, specifically CaCO3, is crucial for oil palm seedling growth. Mycorrhiza presents an effective alternative for nutrient absorption. The study found that mycorrhiza and CaCO3 did not significantly affect plant height and stem girth in oil palms. Lime application especially increased soil pH, with the best treatment being 400 gr of CaCO3 per polybag. Meanwhile, mycorrhiza significantly infected oil palm roots, with the best treatment being 40 gr per polybag. The combination of mycorrhiza and lime did not significantly affect plant growth parameters, but the best treatment was 40 gr of mycorrhiza and 400 gr of lime per polybag.